2021
DOI: 10.1155/2021/8614963
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics and Network Pharmacology-Based Approaches to Explore the Potential Mechanism of the Antidepressant Effect of Cyperi Rhizoma through Soothing the Liver

Abstract: Major depressive disorder (MDD) has become the second most common disease worldwide, making it a threat to human health. Cyperi Rhizoma (CR) is a traditional herbal medicine with antidepressant properties. Traditional Chinese medicine theory states that CR relieves MDD by dispersing stagnated liver qi to soothe the liver, but the material basis and underlying mechanism have not been elucidated. In this study, we identified the active compounds and potential anti-MDD targets of CR by network pharmacology-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…The results showed that quercetin was an active compound that enhanced immune response and glucose metabolism by targeting PAI-1. This study not only revealed the material basis and potential mechanism of CR in the treatment of MDD by soothing liver, but also provided evidence for PAI-1 as a potential target and quercetin as a potential target for MDD treatment (Lei et al, 2021).…”
Section: Anti-depressionmentioning
confidence: 67%
“…The results showed that quercetin was an active compound that enhanced immune response and glucose metabolism by targeting PAI-1. This study not only revealed the material basis and potential mechanism of CR in the treatment of MDD by soothing liver, but also provided evidence for PAI-1 as a potential target and quercetin as a potential target for MDD treatment (Lei et al, 2021).…”
Section: Anti-depressionmentioning
confidence: 67%